2018
DOI: 10.1152/ajplung.00125.2017
|View full text |Cite
|
Sign up to set email alerts
|

Iloprost attenuates hyperoxia-mediated impairment of lung development in newborn mice

Abstract: Cyclooxygenase-2 (COX-2/PTGS2) mediates hyperoxia-induced impairment of lung development in newborn animals and is increased in the lungs of human infants with bronchopulmonary dysplasia (BPD). COX-2 catalyzes the production of cytoprotective prostaglandins, such as prostacyclin (PGI), as well as proinflammatory mediators, such as thromboxane A2. Our objective was to determine whether iloprost, a synthetic analog of PGI, would attenuate hyperoxia effects in the newborn mouse lung. To test this hypothesis, newb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…The right ventricle (RV)-to-left ventricle (LV) free wall thickness ratio was used to estimate right ventricular hypertrophy. Measurement of the RV and LV free wall thickness was done just inferior to the mitral leaflet attachment, as described previously (2,4,23). This measurement is more accurate than the conventional Fulton index of RV/(LV ϩ Septum) weight ratio in newborn mice, as the Fulton index is technically challenging in extremely small newborn mouse hearts.…”
Section: Methodsmentioning
confidence: 99%
“…The right ventricle (RV)-to-left ventricle (LV) free wall thickness ratio was used to estimate right ventricular hypertrophy. Measurement of the RV and LV free wall thickness was done just inferior to the mitral leaflet attachment, as described previously (2,4,23). This measurement is more accurate than the conventional Fulton index of RV/(LV ϩ Septum) weight ratio in newborn mice, as the Fulton index is technically challenging in extremely small newborn mouse hearts.…”
Section: Methodsmentioning
confidence: 99%
“…More importantly, the chest wall contributes significantly to the dissipative and elastic properties of the respiratory tissues (11,31). Notwithstanding, the interpretation of the changes in lung mechanics is often inferred from global respiratory measures, whereas a potentially confounding influence of the chest wall is neglected (19,25,26,28).…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of lung development was associated with a reduction in oxidative stress, NF- κ B expression, and cytokine expression. Previous studies also revealed that caffeine and iloprost improves hyperoxia-induced lung injury through reduction of oxidative stress and inflammation and attenuation of the endoplasmic reticulum stress and mitochondrial dysfunction ( Teng et al., 2017 ; Olave et al., 2018 ; Endesfelder et al., 2019 ). Therefore, we propose that anti-Tn monoclonal antibody improves hyperoxia-induced lung injury in neonatal mice through the suppression of oxidative stress and inflammation, suggesting that anti-Tn antibody may be a promising treatment modality against hyperoxia-induced lung injury.…”
Section: Discussionmentioning
confidence: 93%